Can we prevent boom-bust cycles during euro area accession? - Michał Brzoza-Brzezina; Pascal Jacquinot; Marcin Kolasa (European Central Bank (ECB), 2010)
Euro-area accession caused boom-bust cycles in several catching-up economies. Declining interest rates and easier financing conditions fuelled spending and worsened the current account balance. Over time inflation deteriorated external competitiveness and lowered domestic demand, turning the boom into a bust. We ask whether such a scenario can be avoided using macroeconomic tools that are available in the period of joining a monetary union: central parity revaluation, fiscal tightening or increased taxation. While all these policies can be used to cool down the output boom, exchange rate revaluation seems the most attractive option. It simultaneously trims the expansion of output and domestic demand, reduces the cost pressure and ranks first in terms of welfare.
Keywords: E52; E58; E63; 330; Boom-bust cycles; dynamic general equilibrium models; euro area accession